1993
DOI: 10.3109/01485019308987744
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urinary Levels of Pituitary-Gonadal Hormones in Insulin-Dependent and Non-Insulin-Dependent Diabetic Males with and without Neuropathy

Abstract: Diabetic neuropathies were studied in 100 insulin-dependent diabetes mellitus patients, 314 non-insulin-dependent diabetes mellitus patients with and without an objective evidence of neuropathy (age span, 15-80 years; duration of diabetes distributed over 1-33 years), and their age-matched nondiabetic controls. Serum and urinary levels of pituitary-gonadal hormones were evaluated in the diabetic subjects. There were striking results, i.e., a significantly low serum total and serum free (urinary) testosterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
2
24
2
3
Order By: Relevance
“…Diabetes mellitus is strongly associated with microvascular complications such as neuropathy, retinopathy and nephropathy resulting in organ and tissue damage and these complications are seen in approximately one-third to one-half of people with the disease (23). There has been a significant correlation between the microvascular complications and the testosterone level of these patients and this association has been strongest with diabetic neuropathy (12,22,24). This study also demonstrated a significant correlation with low Prevalence of hypogonadism is significantly higher in newly diagnosed T2DM patients compared to controls.…”
Section: Volume 6 No1 February 2016supporting
confidence: 69%
“…Diabetes mellitus is strongly associated with microvascular complications such as neuropathy, retinopathy and nephropathy resulting in organ and tissue damage and these complications are seen in approximately one-third to one-half of people with the disease (23). There has been a significant correlation between the microvascular complications and the testosterone level of these patients and this association has been strongest with diabetic neuropathy (12,22,24). This study also demonstrated a significant correlation with low Prevalence of hypogonadism is significantly higher in newly diagnosed T2DM patients compared to controls.…”
Section: Volume 6 No1 February 2016supporting
confidence: 69%
“…However, calculated free testosterone may be a better indicator of the free fraction than the free testosterone index, and calculated free testosterone indicates that the difference with nondiabetic men is ϳ10% (24). Hypogonadism was previously shown to be associated with neuropathy (15) and with erectile dysfunction in men with type 1 diabetes (14). Estrone levels were higher in men with diabetes than in control subjects.…”
Section: Gonadal Steroids and Gonadotropinsmentioning
confidence: 99%
“…Several factors, such as insulin treatment, insulin resistance, glucose levels, presence of complications such as neuropathy or retinopathy, age, and sex, are likely to be involved in the explanation of the variation of the results between the different publications. In most studies, testosterone levels did not differ between type 1 diabetes and control subjects (2,3,5,6), except in patients with neuropathy (15) or erectile dysfunction (14) and in adolescents (4), who all had lower levels of total testosterone. Because sex hormonebinding globulin (SHBG) levels are often increased, free testosterone levels may be lower in type 1 diabetes (5,11,12,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigating the hypothalamic-pituitary-gonadal (HPG) axis in T2DM gave conflicting results. Indeed, either hypo-or hypergonadotropic hypogonadism has been reported (2,(8)(9)(10). A recent study demonstrated an association between insulin resistance and a primitive alteration in Leydig cell function in men with various degrees of insulin resistance (11).…”
Section: Introductionmentioning
confidence: 99%